المشتقات المالية وأثرها على عرض السيولة على الإقتصاد الكلي - القريشي، علي حاتم (الأكاديمية العربية للعلوم الإنسانية والتطبيقية, 2020)
Financial derivatives and their impact on liquidity in the presentation macroeconomic. The financial derivatives more topics controversy and versatile, as you can not count raised better and for worse at the macroeconomic level, those tools that stormed the capital markets, and presented Thought Financial, which is no longer Researcher no matter how high the amount be mastered by all, though some may group them in contracts futures and option contracts and futures contracts and swaps. within the framework of financial engineering: have helped invented the collapse of the agreement “Bretton Woods” and fluctuations in exchange rates , which resulted in high rates of inflation at the beginning of the eighties and the accompanying increase in the rates of short-term rates. The successive collapses in the international securities markets in light of the strong competition among financial and banking institutions in the race frantic push these institutions across departments research and innovation to create new financial instruments to manage risks and provide solutions to the problems of financing and jump over the restrictions imposed by the monetary policies.
Keywords: المشتقات المالية -- السياسة المالية -- السيولة المالية -- السياسة الإقتصادية -- الإقتصاد الكلي